1HR ON-CALL — Using Simulated ON-CALL to Underpin Experiential Learning in Final Year Medical Students. Issue 1 (1st January 2020) - Manalayil, J.; Muston, A.; Ball, A.; Chevalier, D.
ABSTRACT: A survey of Blackpool Foundation Year One (FY1) doctors found limited training about being on-call. We could not find any direct mention in Tomorrow's Doctors for preparing undergraduates for this. 1 Working out of hours, on-call and with a reduced workforce is a known area of anxiety among junior doctors. With few examples in literature, 2, 3 we developed a novel approach to aiding final-year medical students prepare for this. A simulated teaching programme allowed students to experience the pressures of working on-call. We hoped to imitate stressors within a safe environment. Students were each given a bleep for an hour. Supervisors role-playing a concerned nurse "bleeped" the students. Each task was held in a folder on different wards (no patient interaction or information was involved). They were relatively simple and designed to stimulate resourcefulness, communication and triage skills. Various resources were available including the number for the medical registrar, played by supervisors. The final station was always the unwell patient aimed at drawing the student immediately to this scenario. A facilitated feedback session explored students' positive and negative experiences, concerns and coping mechanisms. Over the three years of this running, results were resoundingly positive with students taking great confidence from the programme. During the open feedback session, students valued using open wards and having to navigate in an unfamiliar hospital as a realistic preparation for next year. Being on-call is an inevitable part of a junior doctor's work and we believe there is scope for better preparation within undergraduate training. We have developed an effective and sustainable simulation that has shown excellent results. Due to the positive reaction and low maintenance of the project, we aim to cement our teaching programme as a permanent feature for undergraduate students at Blackpool Victoria Hospital.